Evaluation of AviPlus on Growth Performance of Nursery and Growing-Finishing Pigs - W. M. Hutchens; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband; H. I. Calderón; K. Keppy; K. Stephens; P. Maynard (Kansas Agricultural Experiment Station Research Reports, 2020)
This experiment was conducted to determine the effect of AviPlus (a combination of micro-encapsulated sorbic and citric acids and synthetic thymol and vanillin botanicals; Vetagro Inc., Chicago, IL) on growth performance during the wean-to-finish period in a commercial research environment. A total of 1,215 pigs (L337 × 1050; PIC, Hendersonville, TN) were used in a 156-d wean-to-finish experiment. Pigs were weaned at approximately 21 d of age and placed in pens based on initial body weight (BW) with 27 pigs per pen in a randomized complete block design. During the 42-day nursery period, pigs were allotted to 1 of 2 treatments in an unbalanced treatment structure with 15 pens (replications) fed the control diet and 30 pens (replications) fed diets containing AviPlus at 6 lb/ton from d 0 to 21 and 2 lb/ton from d 21 to 42. On d 42, pigs were transported as intact pens from the nursery to the commercial finishing facility. During the finishing period 3 treatments were applied, which included: 1) pigs on the control diet in nursery remained on control diets; 2) 50% of pigs in nursery provided AviPlus were then fed 1 lb AviPlus throughout finishing; and 3) 50% of pigs in nursery provided AviPlus were then fed the control diet throughout finishing. All pens on finishing treatments 2 and 3 were allotted based on ending nursery BW to the finishing treatment. There were 15 replications per treatment in the finishing period. From d 0 to 21, pigs fed diets with AviPlus had a tendency for improved (P<0.058) F/G when compared to pigs fed the control diet; however, there was no evidence of difference (P>0.05) for ADG, ADFI, or d 21 BW. From d 21 to 42, there was no evidence of difference (P>0.05) for ADG, ADFI, or F/G. For the overall nursery period (d 0 to 42), pigs fed diets with AviPlus had improved (P<0.05) F/G when compared to pigs fed the control diet, but there was no evidence of difference (P>0.05) for d 42 BW, ADG, or ADFI between treatments. From d 42 to 106, there was no evidence of difference (P>0.05) for ADG, ADFI, and F/G. However, from d 106 to 156, pigs fed diets containing AviPlus in both the nursery and finishing periods had decreased (P<0.05) ADG when compared to pigs fed the control diet and pigs receiving AviPlus only in the nursery, with no evidence of difference (P>0.05) for other growth responses. For the overall finishing period (d 42 to 156) and overall experimental period (d 0 to 156), there was no evidence of difference (P>0.05) for BW, ADG, ADFI, or F/G. For mortality and removals, there was no evidence of difference (P>0.05) observed during the nursery, finishing or overall. In summary, providing AviPlus during the nursery phase improved early and overall nursery F/G, but there was no effect on overall wean-to-finish performance.
Keywords: AviPlus; Nursery Pigs; Finishing Pigs; Growth Performance